2013
DOI: 10.1111/jcpp.12177
|View full text |Cite
|
Sign up to set email alerts
|

The prevention program for externalizing problem behavior (PEP) improves child behavior by reducing negative parenting: analysis of mediating processes in a randomized controlled trial

Abstract: Background Our indicated Prevention program for preschool children with Externalizing Problem behavior (PEP) demonstrated improved parenting and child problem behavior in a randomized controlled efficacy trial and in a study with an effectiveness design. The aim of the present analysis of data from the randomized controlled trial was to identify the mediating processes that account for these positive treatment effects. We hypothesized that a decrease in negative parenting and increases in positive parenting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 70 publications
5
33
0
2
Order By: Relevance
“…Mechanisms behind change after participation in parenting interventions have mainly been explored through quantitative designs (i.e., moderators and mediator analyses). Some studies have found that changes in externalizing problems are mediated by reductions in negative parenting behaviors (e.g., hitting and yelling) and increases in positive parenting practices (e.g., praise) (Gardner, Burton & Klimes, 2006;Hanisch, Hautmann, Pluck, Eichelberger & Dopfner, 2013). Self-efficacy and parental stress did not mediate this association .…”
Section: Discussionmentioning
confidence: 91%
“…Mechanisms behind change after participation in parenting interventions have mainly been explored through quantitative designs (i.e., moderators and mediator analyses). Some studies have found that changes in externalizing problems are mediated by reductions in negative parenting behaviors (e.g., hitting and yelling) and increases in positive parenting practices (e.g., praise) (Gardner, Burton & Klimes, 2006;Hanisch, Hautmann, Pluck, Eichelberger & Dopfner, 2013). Self-efficacy and parental stress did not mediate this association .…”
Section: Discussionmentioning
confidence: 91%
“…Results of parenting interventions (usually with mothers) in the United States and Europe have demonstrated that improving parenting behaviors can have positive effects on later child adjustment (Guttentag et al, 2014; Hanisch, Hautmann, Plück, Eichelberger, & Döpfner, 2014; Landry, Smith, Swank, & Guttentag, 2008; Watson et al, 2014). The results of this study suggest that parenting interventions with mothers and fathers may have similar effects on child adjustment in Western and non-Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study involving first graders from the same sample used in the current study, showed that harsh discipline correlated with both aggression and oppositional behavior, whereas warmth was only correlated with oppositional behavior (Stormshak, Bierman, McMahon, Lengua, & Conduct Problems Prevention Research Group [CPPRG], 2000). Moreover, in a study examining mediators of a preventive parenting intervention for high-risk preschoolers, harsh parenting, but not warmth, partially accounted for program effects on decreased conduct problems (Hanisch, Hautmann, Plück, Eichelberger, & Döpfner, 2014). Taken together, prior research provides more consistent support for the proximal effects of harsh discipline than warmth on conduct problems.…”
mentioning
confidence: 99%